Seasonal Variations in the Haematological Values of the Nigerian Duck (Anas platyrhynchos) - Olayemi, F.O.; Arowolo, R.O.A. (International Journal of Poultry Science, 2009)
The effects of dry and wet seasons on the blood profiles of the Nigerian duck were determined. This is with a view of elucidating any seasonal variations in these parameters. The haematological values studied included the erythrocyte values (RBC, PCV, Hb., MCH, MCHC and MCV) and the leucocyte values (total and differential leucocyte counts). In the dry season, the duck had higher (p<0.01) RBC counts and PCV values but lower MCH (p<0.05) and MCHC (p<0.001) than in the same bird during the wet season. However, the Hb concentrations were similar in the dry and wet seasons. The total WBC, lymphocyte and heterophil counts were higher (p<0.001) during the dry season than during the wet season. The monocyte and eosinophil counts were however similar in the duck during the two seasons. The study revealed that there were seasonal variations in the haematological parameters of the Nigerian duck. The significance of these results is that caution should be applied when interpreting haematological values of the Nigerian duck in the two different seasons that were investigated, as the values obtained in one season cannot be extrapolated for the other.